Comparison of surgical outcomes between video-assisted anal fistula treatment and fistulotomy plus seton for complex anal fistula: A propensity score matching analysis - Retrospective cohort study. (March 2020) - Liu, Hailong; Tang, Xuan; Chang, Yi; Li, Ajian; Li, Zhen; Xiao, Yihua; Zhang, Yong; Pan, Zhihui; Lv, Liang; Lin, Moubin; Yin, Lu; Jiang, Huihong
Abstract: Background: Video-assisted anal fistula treatment (VAAFT) is a new minimally invasive technique for treating complex anal fistula (CAF). This study aimed to compare the efficacy and safety of VAAFT with fistulotomy plus seton (FPS) for treatment of CAF. Materials and methods: We included 148 patients with CAF receiving surgical treatment at our hospital between January 2017 and December 2018. Propensity score matching (PSM) analysis was conducted with patients' baseline characteristics, and surgical outcomes were compared between the matched groups. Logistic analysis was performed to identify the risk factors for fistula recurrence after VAAFT. Results: Among the study population, 68 and 80 patients underwent VAAFT and FPS, respectively. After PSM, 64 matched pairs of patients were created with no significant differences in baseline characteristics. Compared with FPS, VAAFT had greater efficiency of locating internal openings (90.6% vs. 100%), less intraoperative blood loss (26 ± 15 vs. 12 ± 5 mL), lower incidence of postoperative bleeding (10.9% vs. 1.5%), shorter postoperative hospital stay (6.8 ± 5.1 vs. 5.0 ± 3.3 days), reduced postoperative pain, and decreased wound secretion (all P < 0.05). VAAFT showed a significantly lower Wexner incontinence score than FPS (0.9 ± 1.7 vs. 1.9 ± 2.6, P = 0.003) at 3 months postoperatively, but no significant difference in the healing rate was observed either at 3-month or 1-year ( P = 1.000) follow-up. A total of 12 patients (17.6%) developed fistula recurrence after VAAFT, and logistic analysis revealed that multiple fistula tracts, prolonged operating time and severe postoperative wound secretion were independent risk factors (odds risk = 2.18, 3.25 and 3.04, respectively, all adjusted P < 0.05). Conclusion: Compared with FPS, VAAFT offers some advantages for treatment of CAF, including minimal damage, less pain, rapid recovery, fewer complications and better sphincter preservation. Highlights: Video-assisted anal fistula treatment (VAAFT) may be a better treatment option for complex anal fistula. VAAFT shows less damage, rapid recovery and better sphincter preservation than fistulotomy plus seton. Fistula recurrence after VAAFT is related to multiple fistula tracts, operating time and postoperative wound secretion.